Because of “Because”: Examining the Use of Causal Language in Relative Performance Feedback - Loftus, Serena; Tanlu, Lloyd J. (The Accounting Review, 2018)
ABSTRACT This study examines how the use of causal language in conveying relative performance feedback impacts subsequent task performance. Research in linguistics has shown that causal language, defined as language reflecting the search for reasons (commonly expressed through words such as “because” and “thus”), impacts how recipients process received information. We use a laboratory experiment to show that causal language has a differential effect when used in negative versus positive feedback. In the case where initial relative performance is low, the high use of causal language in the resulting negative performance feedback leads to a greater improvement in subsequent performance, compared to low use of causal language. Conversely, when initial relative performance is high, greater use of causal language in delivering positive feedback results in a smaller improvement in performance. Our results indicate that employees' cognitive processes and reactions to performance feedback are influenced by the language used in explanations.